Forensic Linguistic Analysis of Hate Speech Targeting Jada Smith on Social Media - Dama, Siti Destian Apriliani; Pakaya, Usman; Saud, Jefriyanto (Journal of Advance in Language, Literature, and Education, 2025)
Hate speech on social media necessitates forensic linguistic analysis to decode its legal and societal implications. This study addresses the gap in research on gender-targeted cyber violence against high-profile women, employing descriptive qualitative methods to analyze 26 hate-speech samples directed at Jada Smith from Twitter (2022–2024). Using Canadian legal frameworks (Sections 319, 372 Criminal Code; Human Rights Act), data were categorized via pragmatic, semantic, and syntactic analysis. Findings reveal five hate-speech typologies: defamatory libel (35%, n=9), false messages/harassing communications (27%, n=7), willful promotion of hatred (15%, n=4), public provocation of violence (12%, n=3), and stereotyping (12%, n=3). Dominant tactics include dehumanizing metaphors ("gutter," "road kill"), violent directives ("kill yourself"), and gendered slurs ("bitch"). The study concludes that language weaponization severely damages reputations, with Twitter’s lax moderation exacerbating harm. Forensic linguistics proves vital for legal evidence and platform policy reform.